Le discours des défenseurs des droits des hommes sur la violence conjugale: Une analyse critique - Brodeur, Normand (Service social, 2003)
Se disant victimes d'injustices non reconnues, les défenseurs des droits des hommes dénoncent le discours féministe sur la violence masculine et les politiques sociales mises en place depuis vingt ans pour combattre la violence conjugale. Cet article résume leurs principaux arguments à partir d'une analyse de contenu de trois ouvrages publiés au Québec. La seconde partie de l'article situe ces arguments à l'intérieur des controverses autour de la définition de la violence, de la violence des femmes et du maintien d'un équilibre entre les droits des victimes et ceux des personnes accusées devant les tribunaux. Elle fait aussi état de données qui remettent en question les thèses des défenseurs des droits des hommes sur la symétrie générale de la violence entre les sexes et sur la discrimination systématique dont les hommes seraient victimes au sein du système judiciaire.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; antiféminisme; approches et analyses; canada; couple; cours; discipline; premier cycle; périodes historiques; québec; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; trs1205; violences

Queer theory and communication: from disciplining queers to queering the discipline(s) - Yep, Gust A.; Lovaas, Karen; Elia, John P. (Harrington Park Press, 2003)
Get a queer perspective on communication theory! Queer Theory and Communication: From Disciplining Queers to Queering the discipline(s) is a conversation starter, sparking smart talk about sexuality in the communication discipline and beyond. Edited by members of "The San Francisco Radical Trio," the book integrates current queer theory, research, and interventions to create a critical lens with which to view the damaging effects of heteronormativity on personal, social, and cultural levels, and to see the possibilities for change through social and cultural transformation. Queer Theory and Communication represents a commitment to positive social change by imagining different social realities and sharing ideas, passions, and lived experience. As the communication discipline begins to recognize queer theory as a vital and viable intellectual movement equal to that of Gay and Lesbian studies, the opportunity is here to take current queer scholarship beyond conference papers and presentations. Queer Theory and Communication has five objectives: 1) to integrate and disseminate current queer scholarship to a larger audience-academic and nonacademic; 2) to examine the potential implications of queer theory in human communication theory and research in a variety of contexts; 3) to stimulate dialogue among queer scholars; 4) to set a preliminary research agenda; and 5) to explore the implications of the scholarship in cultural politics and personal empowerment and transformation.
Section: xxx, 415 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; communication; cours; disicpline; premier cycle; périodes historiques; queer; régions géographiques; soc2014; systèmes d'oppressions; thématiques; états-unis